Apakah GCG Berperan Memoderasi Hubungan ESG dengan Nilai Perusahaan di IDX Tahun 2022 - Ervina Chabibatul Choiriyah; Susi Handayani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
ESG is a topic and main concern for investors in making investment decisions. Investors assess the impact of ESG on company performance and ESG cannot be separated from the role of good GCG. With ESG and GCG, it is believed that it can improve company performance. This research was conducted to analyze how Company Value is influenced by ESG, and how GCG moderates the relationship between ESG and Company Value. The research was carried out using quantitative methods, the research population and sample were 78 companies, where the research data was secondary data obtained on the Indonesia Stock Exchange (IDX) website in 2022. The research was carried out using SmartPLS version three. The research results illustrate that ESG has a positive impact on company value, and GCG cannot moderate the relationship between ESG and company value.